Ammonium Impacts Methane Oxidation and Methanotrophic Community in Freshwater Sediment - Yang, Yuyin; Tong, Tianli; Chen, Jianfei; Liu, Yong; Xie, Shuguang (Frontiers in Bioengineering and Biotechnology, 2020)
Lacustrine ecosystems are regarded as one of the important natural sources of greenhouse gas methane. Excess nutrient input can greatly influence carbon cycle in lacustrine ecosystems. Aerobic methanotrophs are a key regulator controlling methane emission. Ammonium is believed to be a critical influential factor of the activity and composition of methanotrophic community, due to its competition with methane as the substrate for aerobic methanotrophs. To date, the ammonium impact on aerobic methanotrophs remains unclear. In the present study, microcosms with freshwater lake sediment were constructed to explore the effect of ammonium level on aerobic methanotrophs. A negative impact of ammonium on aerobic methane oxidation potential and the density of pmoA gene was observed at a very high level of ammonium, while the number of pmoA transcripts was increased by ammonium addition. pmoA gene and transcripts differed greatly in their abundance, diversity and community compositions. pmoA transcripts were more sensitive to ammonium concentration than pmoA gene.